Exploring Public University Undergraduate Students’ Experiencing Intention to Use ChatGPT in Academic Purpose: Application of TAM Theory - Alam, S. M. Ashraful (Journal of Information System and Informatics, 2024)
This study is all about exploring the public university students’ experiencing intention to use ChatGPT in academic purpose with the application of TAM theory along with new extension like enjoyment, informativeness and privacy and security factors. The study was conducted in Rangpur division, Bangladesh. Total 412 data were found valid after data collection. SPSS and Smart PLS software were applied for analysis of the data with TAM theory. The study result shows that, all the factors except perceived enjoyment impacts positively the attitudes of students. Service providers of ChatGPT should consider this factor carefully so that in future they can update some new feature with ChatGPT that may be enjoyable to the users. Teachers of the university should be careful while examining students’ different assignments and projects whether they are not directly copied from ChatGPT or not. Future studies can be with other factors with the existing factors and mediation can also be done by the researchers for further study. School and college level students may be considered for this type of study and the sample size should be larger for better result.